Telemedicine in very elderly patients affected by end-stage Heart Failure: Wishful thinking or real opportunity? - L Mancinelli; M Mazzanti; R Antonicelli (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2022)
Telemedicine is a network of computerization and telecommunication technologies that provides health care services to remote patients. There is increasing evidence that telemedicine interventions are associated with a reduction in hospital admission rates and mortality in patients with heart failure [1,2].